Modeling hydrologic processes associated with soil saturation and debris flow initiation during the September 2013 storm, Colorado Front Range - Timilsina, Sujana, author; Niemann, Jeffrey D., advisor; Rathburn, Sara L., committee member; Nelson, Peter A., committee member (Colorado State University. Libraries, 2019)
Seven days of extreme rainfall during September 2013 produced more than 1,100 debris flows in the Colorado Front Range, about 78% of which occurred on south-facing slopes (SFS). A few previously-published soil moisture observations suggest that SFS were wetter than north-facing slopes (NFS) during the event, which would contrast with soil moisture patterns observed during dry conditions. Various causes have been hypothesized for the preferential saturation of SFS, but those hypotheses remain largely untested. The objectives of this study are to analyze the soil moisture patterns using additional soil moisture observations, determine the hydrologic processes behind the preferential saturation of SFS, and to evaluate the importance of soil moisture in determining the debris flow initiation sites. Soil moisture patterns are simulated using the Equilibrium Moisture from Topography, Vegetation, and Soil (EMT+VS) model for a study region that includes 63% of the observed debris flow locations. Five hypotheses are implemented in the model including: (1) higher rainfall rates, (2) lower interception rates, (3) lower porosity, (4) thinner soils, and (5) reduced deep drainage on SFS. The EMT+VS model is also coupled with an infinite slope stability model to produce factor of safety maps. The hypotheses are tested by comparing the modeled soil moisture patterns to soil moisture observations and the debris flow initiation sites. The results suggest that differences in interception and deep drainage between the slopes were primarily responsible for producing wetter SFS, but the soil moisture pattern likely played a smaller role than vegetation and slope in determining the debris initiation sites.
Keywords: Colorado; soil saturation; vegetation; debris flows; aspect; stability